Patients with adenomatous polyps and carcinomas have increased colonic mucosal prostaglandin E2. Issue 5 (May 1994) - Pugh, S; Thomas, G A
Abstract : Colorectal carcinoma in humans and animal models is associated with increased synthesis of prostaglandin E2 (PGE2). PGE2 synthesis was measured in normal and neoplastic human colorectal mucosa to investigate its role in the adenoma-carcinoma sequence. Paired mucosal biopsy specimens for PGE2 synthesis and histological examination were obtained during 39 diagnostic colonoscopies. Twelve control patients in whom colonoscopies and histology were normal synthesised similar amounts of PGE2 at all sites. Their results were (mean (SD) pg PGE2/mg tissue) caecum 102.8 (15.9) (n = 6), ascending colon 110.8 (24.3) (n = 10), transverse colon 103.9 (19.5) (n = 11), descending colon 102.9 (23.2) (n = 12), sigmoid colon 96.4 (18.0) (n = 12), and rectum 107.1 (17.6) (n = 12). Nineteen patients had a total of 27 adenomatous polyps (rectum (1), sigmoid (22), descending (1), transverse (1), and ascending colon (1): histology-tubular (16), tubulo-villous (8), and villous adenomous (3)). The polyps (178.0 (55.0), n = 27) synthesised more PGE2 than controls (p < 0.001), but the values in polyp-associated mucosa (mean (SD) 115.4 (21.9), n = 15) were not different to control results. Eight patients had carcinomas (rectal (2), sigmoid (4), and caecal (2)) all of which were adenocarcinomas. The cancers (193.6 (40.2), n = 8) synthesised more PGE2 than control specimens (p < 0.001), but were not different to polyps. Cancer-associated mucosa (140.3 (27.7) n = 8) synthesised more PGE2 than control and polyp-associated mucosa. Colorectal neoplasia is associated with a progressive increase in PGE2 synthesis which may have a role in tumourigenesis and be a pathophysiological explanation for the beneficial effects of NSAIDs in animal models and human disease.